Responsibility to protect: an examination of multinational joint task force and the fight against insurgency in the lake Chad Basin, 2009-2017 - Adamu, Abdullahi (2020)
Responsibility to protect denotes, that sovereign states have a responsibility to protect their citizens from mass atrocities crime such as war crime, crime against humanity, ethnic cleansing and genocide. Should the states are unable or unwilling to do so, the responsibility to protect must be undertaken by the international community. As argued in the thesis, the insurgency activities which started as a national security problem for Nigeria has progressively transformed into a regional problem. The crisis creates a considerable humanitarian disaster, not just within Nigeria, but as well as in neighbouring countries that call for swift intervention. Thus, the objectives of the study are: to examine the extent to which the regional peacekeeping of Multinational Joint Task Force succeeded in containing the insurgency within the framework of Responsibility to Protect; to examine whether the collaborative effort of Lake Chad Basin Commission member states hampers or enhances operation of Multinational Joint Task Force; to ascertain the expansion of sub regional peacekeeping demonstrated in Multinational Joint Task Force as the new trend of peacekeeping in transnational conflict situations. Phenomenology was used as a qualitative research method in conducting the study. Hence, 10 informants with vast experience were engaged in a semi structured interview to gather the required data. The thesis found that sub regional peacekeeping of Multinational Joint Task Force has succeeded in containing the insurgency in the Lake Chad Basin due to robust counter insurgency operations of Multinational Joint Task Force. In addition to this, the collaborative effort among the states affected by the insurgency namely, Nigeria, Chad, Niger Republic and Cameroon has enhanced the operational capacity of the Multinational Joint Task Force as demonstrated in intelligence sharing and cross border pursuit. The study also found that success of Multi-National Joint Task Force operations is subjected to adequate funding, appropriate and timely intelligence as well as counter insurgency skills and tactic in an effort to confront the evolving tactics of the violent Islamist group.